Remote Homology Detection in Proteins Using Graphical Models. - Daniels, Noah. (2017)
Abstract: Given the amino acid sequence of a protein, researchers often infer its structure and function by finding homologous, or evolutionarily-related, proteins of known structure and function. Since structure is typically more conserved than sequence over long evolutionary distances, recognizing remote protein homologs from their sequence poses a challenge. We first consider all proteins of known three-dimensional structure, and explore how they cluster according to different levels of homology. An automatic computational method reasonably approximates a human-curated hierarchical organization of proteins according to their degree of homology. Next, we return to homology prediction, based only on the one-dimensional amino acid sequence of a protein. Menke, Berger, and Cowen proposed a Markov random field model to predict remote homology for beta-structural proteins, but their formulation was computationally intractable on many beta-strand topologies. We show two different approaches to approximate this random field, both of which make it computationally tractable, for the first time, on all protein folds. One method simplifies the random field itself, while the other retains the full random field, but approximates the solution through stochastic search. Both methods achieve improvements over the state of the art in remote homology detection for beta-structural protein folds.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Computer Science.; Advisor: Lenore Cowen.; Committee: Donna Slonim, Benjamin Hescott, Bonnie Berger, and Yu-Shan Lin.; Keywords: Computer science, and Bioinformatics.